The effectiveness of coconut coir blanket in controlling slope erosion - Aizat, Mohd Taib @ Taib (2010)
A research to determine the effectiveness of coconut coir blanket in controlling slope erosion was conducted. There were two major division of testing made. One was the material analysis on the soil sample taken and the coconut coir blanket used and another was the simulation of rainfall pouring on sloped surface soil to analyze the erosion rate. Apparently, the division of material testing involved Soil Mechanics Engineering and Light Structure Engineering. Soil Mechanics Engineering assisted this research in soil analyzing in terms of the Soil Classification, Atterberg Limit, Specific Gravity, Shear Strength, Standard Proctor and Direct Shear testing. On the other hand, Light Structure Engineering focused on Tensile Strength of the coconut coir blanket. Generally, the major testing was the simulation of rainfall on the sloped surface soil. The soil sample which was taken from construction site in Bukit Gambang,. Pahang was distributed into four cases. The parameters manipulated were the degree of slope, type of vegetation and the condition of the slope surface. The selected degree of slope were 0°, 400 and 500. The vegetations planted were based on the norm slopes grasses used which were the Signal Grass and Japanese Millet. The conditions of the slope surface were divided into two. They were bare controlled case and protected slope case using coconut coir blanket. The main parameter which was the application of coconut coir blanket as the protection to the slope was proven effective. By comparing the bare controlled slope and the protected slope, the result showed that protected slope using the coconut coir blanket decreases the erosion rate by the Total Suspended Solids (TSS) test conducted. The bare controlled slope collected 0.014345 g/L amount of TSS while protected slope using coconut coir blanket collected only 0.001368 g/L. The difference of 0.0 12977 g/L TSS amount proved that coconut coir blanket was effective in controlling slope erosion assisted by the vegetation of Signal Grass which has longer leaves and gripping fibre roots in increasing the mode of slope strength.